PROXIMATE AND PHYTOCHEMICAL PARAMETERS OF LEAVES OF MEDICINAL PLANT Murraya koenigii - RICHA DODIA*; SUSMITA SAHOO (The Journal of Research ANGRAU, 2022)
The purpose of this research work is to evaluate the proximate and phytochemical components of Murraya koenigii leaves from Vadodara and Anand cities of Gujarat for their efficacy before incorporation into the formulation. Murraya koenigii leaves were collected from June-July in the year 2021. Murraya koenigii leaves have been used to control diabetes. The leaves were evaluated by determining physicochemical parameters including total ash, acid insoluble ash, water-soluble ash, and moisture content. Phytochemical parameters included total phenolic content, total flavonoid content, and total tannin content in terms of gallic acid, quercetin, rutin, and tannic acid equivalents, respectively. The quantitative proximate investigation of Murraya koenigii plant leaves showed leaves of Anand city have a total ash content 15.66±0.32% w/w, acid-insoluble ash 0.59±0.01% w/w, moisture content 1.12±0.03% w/w respectively compared to Vadodara city total ash content 12.29±0.08% w/w, acid-insoluble ash 0.20±0.02 %w/w, moisture content 1.31±0.12 %w/w, respectively. However, Anand city leaves have a lower water-soluble capacity of 0.91±0.06% w/w compared to Vadodara city at 7.34±0.40% w/w. In this study, leaves of Vadodara city showed a high quantity of total phenolics, total flavonoids, and total tannin phytoconstituents 101.50±0.92 mg of GAE/g, 163.83±0.87 mg of RT /g, 128.16±0.76 mg of TAE/g compared to Anand city 61.58±0.62 mg of GAE/g,126.66±1.04 mg of RT / g, 64.16±1.44 mg of TAE/gconcerning gallic acid, rutin, and tannic acid. However, the leaves of Anand city showed a high quantity of total flavonoids 101.16±1.28 mg of QE/g compared to Vadodara city at 59.0±0.09 mg of QE/g concerning quercetin